Constitutional and Legal Framework of Women Empowerment in India - Ashok Kumar Behera (Universitas Negeri Semarang, 2021)
Our Constitution as ultimate law of territory and sufficient of legislations tried to reorganize their surroundings and supply assistance for security and their upliftments.Â The study is an attempt to review and fall out that there is complete constitutional and other legal arrangement to deal with issues of women empowerment. However, this research paper is limited to some legal provisions and interpretations of Indian Courts only. The jurisprudence of industrialization has confirmed the very important roles as tool of social justice. Equal Remuneration Act 1976 passed with the aim of equal pay for equal work both man and woman and contained that there will be no intolerance against employment of woman and promotes chance to them. Maternity Benefit Act 1961 provides protection to women workers maternity leave, extra leave for child infancy sufficient awareness to their security and strength of woman during pregnancy and lactation. Factories Act 1948 makes comprehensive requirements concerning health, safety and welfare of employment of women. Sec.25 of Beedi and Cigar Workers (Condition and Employment) Act 1966 laid down no woman shall be obligatory to manufacturing premises except between 6 a.m. and 7 a.m. and to make sure for safety of woman.